(untitled) (International Journal of Communication Systems and Network Technologies, 2017)
The power system need to be operated economically and with cost efficiency. In this paper application of new bio-inspired metaheuristic named as Bird Swarm Algorithm (BSA) has been adopted for the optimization of ELD problems in power system operation. The concept has been conceived from the flocking behavior of birds. Birds mainly have three kinds of behaviors i.e. foraging behavior, vigilance behavior and flight behavior. Therefore by the implementation of social behavior, social interaction and swarm intelligence, BSA has been formulated for economic load dispatch problems.